GERAKAN MAHASISWA SURABAYA SEBAGAI UPAYA PENINGKATAN KESADARAN MASYARAKAT TERHADAP PENGELOLAAN SAMPAH SUNGAI BERBASIS IMPLEMENTASI ASSET-BASED COMMUNITY DEVELOPMENT (ABCD) - Ayu Safitri, Feby Salma; Nurul Izzah, Nazwa; Sulani, Sulani; Catur Rizky, Muhammad; Arifin, Samsul (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Efforts to improve environmental quality through cleanliness and greening activities on campus are an important strategy to foster students’ awareness and active participation. These activities not only enhance poorly maintained environments but also cultivate collective responsibility and create a healthier and more comfortable campus atmosphere. In line with this, the Surabaya Student Movement held on October 3, 2025, aimed to raise public awareness about prohibiting waste disposal into rivers through socialization, environmental education, and collaborative communi ty work. The program applied the Asset-Based Community Develop ment (ABCD) approach, utilizing community potential and partici pation as key assets. Socialization focused on understanding waste types, waste segregation, and implementing the principles of reduce and reuse. The results showed positive community responses, redu ced potential for pollution and flooding, and increased awareness in waste management. This program is considered effective and can be replicated in other areas facing similar environmental challenges.